2003
DOI: 10.1016/s1631-0713(03)00054-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term thermal evolution and effect of low power heating in an underground quarry

Abstract: Vertical profiles of temperature have been monitored in the atmosphere of an underground quarry since June 2001. A longterm temperature increase of the order of 0.1 • C per year is observed. Three heating experiments with 100-W sources, performed to study plume dynamics, can also be used to investigate the effect of visits on this increase. Ten days after the 24-h heatings, the initial state is not restored. Artificial contributions to the observed long-term temperature trend, triggered by internal heat releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…1), as well as three other locations: two points N2 and N3 intermediate between the two rooms, and one point (B20) in the southernmost part. One room, referred to as ''room 15'', was selected to perform heating experiments (CROUZEIX et al, 2003;2006a, b) and, in July 2003, was equipped with a thermally insulating wall (styrofoam TM ) to restrict air currents and ventilation with the rest of the quarry. The partition defines a volume of 216 m 3 (mean width 9 m, height 2 m and length 12 m), with a total wall surface area of 282 m 2 .…”
Section: Experimental Set-ups In the Vincennes Quarry And The Paris Omentioning
confidence: 99%
“…1), as well as three other locations: two points N2 and N3 intermediate between the two rooms, and one point (B20) in the southernmost part. One room, referred to as ''room 15'', was selected to perform heating experiments (CROUZEIX et al, 2003;2006a, b) and, in July 2003, was equipped with a thermally insulating wall (styrofoam TM ) to restrict air currents and ventilation with the rest of the quarry. The partition defines a volume of 216 m 3 (mean width 9 m, height 2 m and length 12 m), with a total wall surface area of 282 m 2 .…”
Section: Experimental Set-ups In the Vincennes Quarry And The Paris Omentioning
confidence: 99%
“…A first set of experiments was performed from February to May 2002 in an open room of the underground quarry of Vincennes, near Paris [18]. Low power heat sources were used (100 W), and temperature was measured in the air and in the rock at different heights.…”
Section: Introductionmentioning
confidence: 99%
“…In order to introduce minimal perturbations, Cassini entered the room always alone, holding a weak candle and remaining only the short time needed to read both thermometers. Thus, Cassini was aware of the thermal effect associated with a person, which corresponds to a power of the order of 100 W, a value large enough to produce lasting thermal effects in the delicate underground environment (Crouzeix et al, 2003). The temperature at the surface was also measured.…”
Section: Paris Observatory Underground Datamentioning
confidence: 99%
“…In addition, temperature records in the underground galleries of the Paris Observatory were possibly affected by the presence of a heat source (petrol lamp) from 1912 to 1917. Recent experiments (Crouzeix et al, 2003) indeed indicated that a low power heat source can have lasting effects in underground settings, possibly longer than ten times the heating duration.…”
Section: Introductionmentioning
confidence: 99%